Odnos medicinskih sester do pacienta, odvisnega od prepovedanih drog - Perviz, Amal (Obzornik zdravstvene nege, 2021)
Introduction: The attitude of nurses towards patients addicted to illicit drugs is one of the factors that affects both the outcome of treatment and the rehabilitation of patients addicted to illicit drugs. The objective of this study is to investigate the attitude of nurses towards the treatment of patients addicted to illicit drugs. Methods: We analyzed and synthesized reviewed evidence, which were collected in the CINAHL, ProQuest Dissertations & Theses Global, SpringerLink, WILEY, and PubMed. The search limiting criteria were: the publication of articles between 2008 to 2018 and articles available in the English language. We created a PICOT conceptual model using the following keywords: nurses, substance use disorders and attitudes. The assessment of the quality of evidence is shown in the hierarchy of evidence. The data were processed with a thematic qualitative analysis. Results: We reviewed 18 relevant articles to identify 68 codes, which can be classified into 5 content categories: (1) factors of influence on negative interpersonal relationships, (2) factors of influence on positive interpersonal relationships, (3) psychopathological, behavioral, and other factors on part of the patient, which all have a significant impact on the quality of interpersonal relationships, (4) the consequences of an inadequate attitude of nurses towards patient care, and (5) the measures for preventing prejudice and stigmatization of patients addicted to illicit drugs. Discussion and conclusion: The study has confirmed a negative attitude of nurses towards patients addicted to illicit drugs. Certain factors are related both to negative and positive attitudes of nurses towards patients addicted to illicit drugs. Studying these factors and their consequences on nursing care received by patients addicted to illicit drugs, however, requires additional research.
Keywords: abuse; droge; drugs; medicinske sestre; nurses; nursing; odvisnosti; psihoaktivne snovi; psychoactive substances; stigma; zdravstvena nega; zloraba